Assessment of beneficial fungal microorganism’s bio-efficacy in stimulating morphological and physiological parameters of Allium cepa plants grown in soil amended with fish wastes - Reda E. Abdelhameed; Rabab A. Metwally (BMC Plant Biology, 2022)
Abstract Background The increase in the human consumption of fish results in the production of organic fish wastes (FW). For enhanced soil fertility and plant growth at a lower cost and without the negative impacts of chemical fertilizers, these wastes could be employed as a valuable organic fertilizer. To determine the synergistic bio-efficacy of Trichoderma sp. and arbuscular mycorrhizal (AM) fungi in stimulating the morphological and physiological characteristics of FW-fertilized Alium cepa, as well as to investigate their involvement in boosting soil fertility, the current study was carried out. Overall, eight treatments were applied as follows: AM, Trichoderma sp., AM + Trichoderma sp., FW, AM + FW, Trichoderma sp. + FW, AM + Trichoderma sp. + FW, and control. Growth and physiological assessments of onion plants were taken after 8 weeks from FW application. Results Our results showed that FW application combined with AM fungi and Trichoderma sp. inoculations increased aggregate stability of the soil (glomalin content) and soil chitinase activity. Moreover, using the bio-inoculations along with FW amendments significantly (p < 0.05) improved the photosynthetic pigments, protein, carbohydrates, and nutrients content of onion plants. It's interesting to note that the triple interaction of AM + Trichoderma sp. + FW led to the greatest increase in plant height, root length, number of leaves, and leaf area as well as total fresh and dry weights of shoots and roots. Besides, AM fungal colonization was at its highest percentage with Trichoderma sp. inoculation, although this percentage decreased with FW addition. Conclusion We concluded that the combined treatments of AM fungi and Trichoderma sp. along with FW application to the soil can be proposed as a successful strategy for plant performance in nutrient-deficient soils as both fungal inoculants are capable of degrading these wastes and converting them into manure suitable for farming so plants can uptake the minerals effortlessly.